Pengendalian Risiko Ergonomi Kasus Low Back Pain pada Perawat di Rumah Sakit - Kurniawidjaja, L. Meily; Purnomo, Edy; Maretti, Nadia; Pujiriani, Ike (Faculty of Medicine, Universitas Padjadjaran, 2014)
Perawat berisiko tinggi nyeri pinggang bawah. Tujuan penelitian ini menilai faktor risiko akivitas fisik dan sarana kerja yang dominan dapat menimbulkan low back pain (LBP) pada perawat di ruang Rawat Inap dan Unit Gawat Darurat Rumah Sakit di Jakarta serta memberikan rekomendasi pengendalian risiko LBP. Observasi dilakukan untuk mengidentifikasi aktivitas berisiko tinggi LBP, metode rapid entirebody assessment (REBA) menilai tingkat risiko ergonomi, kuesioner dan Nordic body map menilai faktor risiko lainnya serta keluhan LBP, desain potong lintang untuk analisis asosiasi, pengukuran dan analisis untuk menilai alat kerja. Hasil penelitian mendapatkan prevalensi LBP cukup tinggi pada perawat UGD di RSUD Tarakan tahun 2013 (61,1%) dan perawat rawat inap di RS Bhayangkara tahun 2012 (31,8%), namun rendah pada perawat UGD di RSS bila dibandingkan dengan hasil survei global (43,1–87%); aktivitas yang dominan menimbulkan LBP adalah membungkuk dan angkat angkut pasien. Didapatkan hubungan yang bermakna postur membungkuk (p=0,031; OR=1,18–133,89), sudut lengkung punggung (p=0,024; OR=1,65-196,31), dan transfer pasien (p=0,011; OR=5,22–176,83) dengan tingkat risiko LBP. Simpulan, aktivitas fisik perawat dan sarana kerjanya dapat menyebabkan LBP sehingga disarankan menyediakan sarana kerja yang adjustable serta ‘meja’ dinding di toilet untuk pengukuran urin, memenuhi rasio perawat-pasien minimal, SOP, mendidik perawat agar mampu melakukan pengendalian.. Kata kunci: Ergonomi, low back pain, perawatErgonomic Risk Control on Low Back Pain among Hospitals' NursesAbstract Nurses are at high risk of low back pain (LBP). This study aimed to assess physical activities and working facilities as the risk factors that can lead to LBP in nurses in the wards and the emergency units of several hospitals in Jakarta to provide recommendations for controlling the risk of LBP. Observations were performed to identify high-risk activities and the rapid entire body assessment (REBA) method was used to assess the ergonomic risk. Questionnaires and Nordic body map were also used to assess the other risk factors and LBP-related complaints. In addition, the cross-sectional design for association analysis, measurement and analysis to assess the working tools were also applied. The results showed that the prevalence of LBP among nurses was higher in the RSUD Tarakan emergency unit in 2013 (61.1%) and RS Bhayangkara wards in 2012 (31.8%). In the private hospital emergency unit, the LBP is lower compared to the results of a global survey (43.1–87%). The dominant causes of LBP were bending and patient-lifting. A significant association was evident between the risk level of LBP and bending posture (p=0.031, OR=1.18–133.89), curved spine angle (p=0.024, OR=1.65–196.31), and patients transfer (p=0.011, OR=5.22–176.83). In conclusion, nurse physical activities and their work facilities can induce LBP. Therefore, it is suggested to provide adjustable facilities and wall-mounted tables in the toilets for urine measurements. Meeting the the minimum nurse: patient ratio, providing SOPs, and educating the nurses to control the risks of LBP are also needed.Key words: Ergonomic, low back pain, nurse DOI: 10.15395/mkb.v46n4.342